2022
DOI: 10.1186/s40942-022-00401-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of brolucizumab versus aflibercept in patients with neovascular age-related macular degeneration: a randomized trial in Indian patients

Abstract: Background The current standard treatment for neovascular age-related macular degeneration (nAMD) involves intravitreal injections of anti-vascular endothelial growth factor (anti-VEGF) agents. The aim of the present study was to compare the effectiveness and safety of two anti-VEGF drugs: brolucizumab and aflibercept, in treatment-naïve nAMD Indian patients over a period of 48 weeks. Methods A prospective, randomized, single-centre, single-blinded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…This retrospective study compared clinical efficacy and adverse event following intravitreal brolucizumab injection compared to aflibercept in treatment-naive nAMD patients during loading-phase treatment. In previous studies, brolucizumab resulted in similar BCVA improvement and CMT reduction but greater central choroidal thickness reduction than af libercept [14,15,18]. In the present study, BCVA was significantly improved and CMT was significantly decreased in both groups.…”
Section: Discussionsupporting
confidence: 75%
“…This retrospective study compared clinical efficacy and adverse event following intravitreal brolucizumab injection compared to aflibercept in treatment-naive nAMD patients during loading-phase treatment. In previous studies, brolucizumab resulted in similar BCVA improvement and CMT reduction but greater central choroidal thickness reduction than af libercept [14,15,18]. In the present study, BCVA was significantly improved and CMT was significantly decreased in both groups.…”
Section: Discussionsupporting
confidence: 75%
“…Similarly, a Spanish study found that dry AMD is more prevalent than wet AMD [9]. However, the prevalence of wet AMD is twice as high as that of dry AMD in some other studies [15,16].…”
Section: Discussionmentioning
confidence: 89%
“…This is in accordance with previous literature. Mishra et al demonstrated that both IRF and SRF were detected in 82.1% of patients at baseline; after the loading phase, they reduced respectively to 41.1% and 16.1% 22 . Toto et al 18 showed a reduction in IRF and subfoveal-SRF rates in type 1 MNV between baseline and week 12, respectively changing from 41.7 to 20.8% and from 62.5 to 4.2%.…”
Section: Discussionmentioning
confidence: 99%